The Relation between Erythrocyte Trans Fat and Triglyceride, VLDL- and HDL-Cholesterol Concentrations Depends on Polyunsaturated Fat - Kabagambe, Edmond K.; Ordovas, Jose M.; Hopkins, Paul N.; Tsai, Michael Y.; Arnett, Donna K. (PLOS ONE, 2012)
Background Trans fatty acids (TFA) lower HDL and increase triglyceride concentrations while polyunsaturated fatty acids (PUFA) lower triglycerides and may decrease HDL concentrations. The effect of the interaction between trans fat and PUFA on lipids is uncertain. Methods Men and women (n = 1032) in the Genetics of Lipid-Lowering Drugs and Diet Network (GOLDN) study were included. Fatty acids in erythrocyte membranes were measured with gas chromatography while data on potential confounders were obtained from questionnaires. To test the interaction between total erythrocyte PUFA (ePUFA) and TFA (eTFA) on lipid concentrations we distributed eTFA into tertiles and dichotomized ePUFA at the median concentration. Results For the 1st, 2nd and 3rd tertiles of eTFA, multivariate-adjusted means±s.e.m for HDL were 46.2±1.1, 46.3±1.1 and 45.5±1.0 mg/dL among those with low ePUFA, respectively, while they were 50.0±1.1, 46.9±1.1 and 44.7±1.1 mg/dL among those with high ePUFA, respectively (P for interaction = 0.01). For the 1st, 2nd and 3rd tertiles of eTFA, multivariate-adjusted means±s.e.m for triglycerides were 178.6±11.3, 144.7±10.9 and 140.8±10.6, respectively, among those with low ePUFA, while they were 133.8±11.3, 145.7±10.9 and 149.3±11.5, respectively, among those with high ePUFA (P for interaction = 0.005). Results for VLDL were similar to those for triglycerides. No significant interactions were observed for LDL or total cholesterol. Conclusions The relation between trans fat and HDL, VLDL and triglycerides may depend on PUFA. The benefit of avoiding trans fat may be greater among individuals with higher PUFA intake. Supplementation with PUFA among individuals with relatively high trans fat intake may have limited benefits on lipid profiles.